How is a Service Development Simulation Exercise Useful? A Student-Centered Perspective - Spiteri, Damian (Research in education (Manchester), 2013)
This paper appraises a simulation activity which forms part of the post-graduate social work curriculum offered at the University of Strathclyde. It shows how simulations that are based on activities that are as close as possible to actual ‘real-life’ situations can be applied as a teaching strategy so as to enable students to integrate knowledge, skills and critical thinking in the social work field. It presents the students' appraisal of the module and aims to generate insights about its suitability for application to a wide range of training courses, including those of education, health, social care and any of the applied social sciences. The study was undertaken by observing and interacting with the students while they set and completed relevant tasks and by extrapolating relevant data from the ‘evaluation sheets’ that they filled in at the end of the module. The paper shows that the students were introduced to perspectives of the subject matter that they had not thought about previously. It also provided them with an opportunity to apply theory to a practice situation in a manner that further consolidated their overall social work training.